2020
DOI: 10.29086/978-0-9869936-1-9/2020/aasbs02
|View full text |Cite
|
Sign up to set email alerts
|

Alternation African Scholarship Book Series #02 (2020) Technology-based Teaching and Learning in Higher Education during the Time of COVID-19

Abstract: Alternation research groups have made decisive and far-sighted knowledge production Technology-based Teaching and Learning in Higher Education during the Time of COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…From the data, it was evident that the utilisation of ICT tools for teaching and learning purposes is indeed an area that necessitates action, since one has to make the decision to remain with the status quo or embrace change and move into the future (Du Plessis 2016, 2018Du Plessis and Blignaut 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From the data, it was evident that the utilisation of ICT tools for teaching and learning purposes is indeed an area that necessitates action, since one has to make the decision to remain with the status quo or embrace change and move into the future (Du Plessis 2016, 2018Du Plessis and Blignaut 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, educational institutions have to be ready to switch to hybrid or fully online teaching at any moment (which can jeopardize the planned field-related activities). Therefore, VFTs may be the only option available (Sershen et al, 2020). The research conducted by Ip et al (2019) showed that immersive VFTs could be successfully integrated into a geography-related online course.…”
Section: Using Immersive Vfts As a Substitution For Traditional Field...mentioning
confidence: 99%
“…However, traditional (actual) fieldrelated activities are often underutilized due to logistical considerations, financial expenses, and safety constraints, as well as inclusion issues since fieldwork locations may be inaccessible for students with disabilities (Friess et al, 2016;Wallgrün et al, 2019;Zhao et al, 2020). The current COVID-19 pandemic made the situation even worse since the majority of schools and universities postponed, reduced, or completely canceled planned excursions and fieldwork activities (Sershen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We should also note that the current situation with the COVID-19 pandemic is likely to introduce significant changes in education and the wider world. The AR/ VR technology will likely gain in importance as a mechanism for students to experience field trips and fieldwork activities "virtually" if they are unable to visit in person [28]. Opportunities to combine face to face and online environments will also influence HE teaching.…”
Section: Final Pointsmentioning
confidence: 99%